Syndecan-1 is a Key Mediator of Entosis and Cellular Competition in Pancreatic Cancer - Li, Kara; Li, Chenyang; Umeda, Shigeaki; Kappagantula, Rajya L; Paku, Masakatsu; Zeng, Yue; Iacobuzio-Donahue, Christine; Yao, Wantong (Pancreas, 2025)
Entosis, a form of cell-in-cell (CIC) structure formation where one cell invades and becomes internalized by another, has long been observed in various malignancies and is considered a critical cellular process in cancer progression, with potential impacts on tumor heterogeneity, survival, and metastasis. Syndecan-1 (SDC1), a transmembrane proteoglycan involved in cell adhesion and communication, plays a pivotal role in these processes, yet its specific function in entosis within pancreatic ductal adenocarcinoma (PDAC) remains underexplored. This study aimed to investigate whether SDC1 facilitates entosis in PDAC cells and to assess its impact on tumor aggressiveness and patient outcomes. Using immunohistochemistry, flow cytometry, and entosis assays, our findings reveal that SDC1 prominently localizes at cell-cell contact points, facilitating stable intercellular adhesion and promoting entotic activity. Knockdown experiments reveal that reduced SDC1 expression significantly diminishes CIC formation, implicating SDC1 as a critical mediator of this process. Analysis of clinical samples revealed that high SDC1 expression correlates with increased entotic activity in PDAC tumors and is associated with decreased patient survival. These results suggest that SDC1-mediated entosis enhances tumor aggressiveness by contributing to cellular competition and heterogeneity. Our study sheds light on the critical role of SDC1 in promoting CIC formation and cancer progression, highlighting its potential as a therapeutic target to disrupt entotic mechanisms in PDAC.